First description of clinical presentation of piscine orthoreovirus (PRV) infections in salmonid aquaculture in Chile and identification of a second genotype (Genotype II) of PRV. Issue 1 (December 2016) - Godoy, Marcos; Kibenge, Molly; Wang, Yingwei; Suarez, Rudy; Leiva, Camila; Vallejos, Francisco; Kibenge, Frederick
Abstract Background Heart and skeletal muscle inflammation (HSMI) is an emerging disease of marine-farmed Atlantic salmonSalmo salar, first recognized in 1999 in Norway, and recently associated with piscine orthoreovirus (PRV) infection. To date, HSMI lesions with presence of PRV have only been described in marine-farmed Atlantic salmon in Norway. A new HSMI-like disease in rainbow troutOncorhynchus mykiss associated with a PRV-related virus has also been reported in Norway. Methods Sampling of Atlantic salmon and coho salmon was done during potential disease outbreaks, targeting lethargic/moribund fish. Fish were necropsied and tissues were taken for histopathologic analysis and testing for PRV by RT-qPCR assay for segment L1 and conventional RT-PCR for PRV segment S1. The PCR products were sequenced and their relationship to PRV strains in GenBank was determined using phylogenetic analysis and nucleotide and amino acid homology comparisons. Results The Atlantic salmon manifested the classical presentation of HSMI with high PRV virus loads (low Ct values) as described in Norway. The coho salmon with low Ct values had myocarditis but only in the spongy layer, the myositis of red muscle in general was mild, and the hepatic necrosis was severe. Upon phylogenetic analysis of PRV segment S1 sequences, all the Chilean PRV strains from Atlantic salmon grouped as sub-genotype Ib, whereas the Chilean PRV strains from coho salmon were more diversified, grouping in both sub-genotypes Ia and Ib and others forming a distinct new phylogenetic cluster, designated Genotype II that included the Norwegian PRV-related virus. Conclusions To our knowledge the present work constitutes the first published report of HSMI lesions with presence of PRV in farmed Atlantic salmon outside of Europe, and the first report of HSMI-like lesions with presence of PRV in coho salmon in Chile. The Chilean PRV strains from coho salmon are more genetically diversified than those from Atlantic salmon, and some form a distinct new phylogenetic cluster, designated Genotype II.